Implementasi IoT pada Sistem Pemantauan Level Air Menggunakan ESP32 dan Platform Antares - Diono; Muhammad Syafei Gozali; Tri Guntoro, Hendra (JURNAL INTEGRASI, 2026)
This research develops an Internet of Things (IoT)-based water level monitoring system that can work in real-time both locally and online. The system is designed using an ultrasonic sensor integrated with an ESP32 microcontroller to process and send data to the Antares platform via the MQTT protocol. The obtained data can be displayed via the Antares dashboard and an I2C LCD as a local display, equipped with LED indicators and a buzzer as a warning when the water level is below the 65 cm threshold. To maintain communication stability, a static IP configuration is used. Test results show that the system has high accuracy with an average error of 0.2 cm, a delay of 129.15 ms, and no packet loss, thus being able to provide reliable performance. Thus, this system is considered effective, efficient, and suitable for application in monitoring water levels for various industrial needs.